Evaluation of Implant Survival by Analysing Dental Panoramic Radiographs: 10-Year Retrospective Study - Aydin Kader Cesur; Gaş Selin (Balkan Stomatological Society, 2021)
Background/Aim: Panoramic radiographs have been used widely for pre-implant evaluation and the preparation of treatment protocols. Panoramic radiography is often the first choice method for the implant placements because it gives information on the overall shape of the jaws, the position of the maxillary sinus floor and the nasal cavity floor, and vertical position of the mandibular canal and the mental foramen in relation to dental implants. The specific aim of the present study was to evaluate 10-year survival rate of dental implants by analysis of dental panoramic radiographs.